Analysis of Water Availability in the Sapucaí River Basin, São Paulo Slope, Brazil - Araújo, Renata Ribeiro de; Silva, Janaira dos Santos; Rizk, Maria Cristina (Technical and Scientific Journal Green Cities, 2025)
This article presents the analysis of water availability in the Sapucaí River basin, on the São Paulo slope, Brazil. To this end, the requirements for water uses from the Electronic Grant System database on the website of the Department of Water and Electric Energy (DAEE), of the State of São Paulo, Brazil, which were granted on the day of data collection on March 15, 2024, were used. The uses evaluated were surface abstraction, surface release and damming. The methodology consisted of estimating the demand for the granted water, through the sum of the flows in m³/hour of surface abstractions and releases. To carry out the study of the water behavior of the hydrographic basin, the minimum reference flows Q7, 10 and Q95 were estimated, in m³/hour, using the BCDAEE2000 Regionalization software, which consists of a tool developed by the DAEE capable of calculating the minimum reference flows based on the rainfall and fluviometric database. The results showed that the watershed is in a critical situation in relation to Q7,10 and in a worrying situation in relation to Q95, evidencing the need for new management strategies and conservation measures. This work is part of a theoretical gap related to critical watersheds, contributing with a relevant analysis of water resources management and offers subsidies for the formulation of strategies aimed at the sustainability of the watershed.
Keywords: Water availability; Water Resources Management; Water Balance